Local Wisdom Batak Toba and Nias Related to Chemical Content - Simanjuntak, Akezia (Journal of Tropical Chemistry Research and Education, 2024)
This article talks about the local wisdom of the Batak Toba and Nias with the subject of chemistry. This article uses a qualitative method. The data collection techniques used are interview techniques and documentation, where the resource persons in this research are Selamat Sihombing (Batak Toba) And Gatina Halawa (Nias). The relationship between Toba Nias Batak culture and Chemistry shows that there is a tight relationship between culture and Chemistry. So every culture has good chemical elements in its manufacture, mixing, and so on., the results studies obtained conclusions of chemistry are all around us and also in the local wisdom of the Batak Toba and Nias.